Estrutura genética do vector de malária Anopheles atroparvus em Portugal: implicações num contexto de aquecimento global - salgueiro, P.; C. Sousa; Vicente, J; do Rosário V.; PintoJ (II Workshop Clima e Recursos Naturais – Bragança, Portugal ‐ 15 a 19 de Novembro 2010 – Livro de Acta, 2010)
With the present state of environmental and climate change, there is a growing concern about (re) emerging diseases, particularly those that are vector-borne. Of these, malaria is the vector-borne disease with the highest impact on human population. In a potential scenario of malaria resurgence in Europe, the rate of transmission of Plasmodium parasites will be most certainly affected by patterns of structure and connectivity among vector populations. This is the main subject of the present work, regarding the former malaria mosquito vector in Portugal, Anopheles atroparvus. Thus, we genotyped 10 microsatellite markers in mosquitoes collected at 10 sites in Portugal, between 1993 and 2008. Our data suggest a widespread gene flow over the country, and a positive correlation between geographical distances and genetic differentiation among A. atroparvus populations. Estimates of effective population size (Ne) based on temporal samples ranged between 1990 and 12197. Tests of "bottleneck effect" suggest a population contraction in almost all populations sampled. These results can be explained by the intensive anti-vector campaign taken in the past (until 1970s). This present population structure assessment of A. atroparvus in Portugal constitutes the background knowledge of the last 15 years. We recommend that the assessment of ecological, biological and genetic parameters of sentinel-localities should be maintained in the future. These should include areas of tourism and with migrant human populations.